2009
DOI: 10.1143/jjap.48.091401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Concentration on Characteristics of Ba(Zr0.1Ti0.9)O3Thin Films Deposited on Indium Tin Oxide/Glass Substrates

Abstract: In this study, the perovskite Ba(Zr 0:1 Ti 0:9 )O 3 (BZ1T9) ferroelectric thin films deposited on indium tin oxide (ITO)/glass substrates for applications in system-on-panel (SOP) devices are produced and investigated. The optimal sputtering conditions of as-deposited BZ1T9 thin films are an rf power of 160 W, a chamber pressure of 10 mTorr, a substrate temperature of 580 C, and an oxygen concentration of 40%. The effect of oxygen concentration on the physical and electrical characteristics of BZ1T9 thin films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This result was attributed to the defects and oxygen vacancies in as-deposited manganese oxide thin films on ITO substrates. 7,28) Figure 8 shows the typical I-V characteristics of the CTA-treated manganese oxide RRAM device with positive bias, with ln I on the vertical axis and ln V on the horizontal axis. The CTAtreated manganese oxide thin films also exhibited ohmic conduction for 0.1 to 3 V. In addition, the smaller number of oxygen defects and vacancies in the CTA-treated manganese oxide thin films of the RRAM devices was proved by the ln I-V 1/2 curve.…”
Section: Resultsmentioning
confidence: 99%
“…This result was attributed to the defects and oxygen vacancies in as-deposited manganese oxide thin films on ITO substrates. 7,28) Figure 8 shows the typical I-V characteristics of the CTA-treated manganese oxide RRAM device with positive bias, with ln I on the vertical axis and ln V on the horizontal axis. The CTAtreated manganese oxide thin films also exhibited ohmic conduction for 0.1 to 3 V. In addition, the smaller number of oxygen defects and vacancies in the CTA-treated manganese oxide thin films of the RRAM devices was proved by the ln I-V 1/2 curve.…”
Section: Resultsmentioning
confidence: 99%
“…However, the (111) peaks of BZ1T9 thin films were not observed for (400) and (440) ITO substrates. Therefore, we determined that the crystallinity and deposition rate of BZ1T9 thin films on ITO substrates differed from those in these study [24][25][26][27].…”
Section: Abo 3 Pervoskite Structure Materials Systemmentioning
confidence: 85%
“…The XRD patterns of BZ1T9 thin films with 40% oxygen concentration on Pt/Ti/SiO 2 /Si substrates from our previous study were shown in Fig. 1 [24][25]. The (111) and (011) peaks of the BZ1T9 thin films on Pt/Ti/SiO 2 /Si substrates were compared with those on ITO substrates.…”
Section: Abo 3 Pervoskite Structure Materials Systemmentioning
confidence: 99%
“…The as-deposited films annealed by the rapid temperature annealing (RTA) processing would be reported extensively. Many studies had been reported that rapid temperature annealing method was successfully to increase the electrical and physical properties [7][8][9].…”
Section: /[212]mentioning
confidence: 99%